Minimal prime ideals in seminearrings. Issue 1 (May 2021) - Senthil, S; Perumal, R
Abstract: This paper deals with the properties of ideals in seminearrings with special reference to right duo seminearrings. We formulate the concept of prime ideal and minimal prime ideal in a seminearring. In the case of Noetherian right duo seminearring, we derive some additional properties.